Evaluating the competent use of EAP linguistic features in relation to CEFRL English levels - Mª Pilar Durán Escribano; Ana Luz Rubio Moreda (Revista de Lingüística y Lenguas Aplicadas)
The purpose of this study is to analyse the competent use of EAP linguistic features (passive voice, use of nominal groups, typical verb forms, and modality), by the Technical University of Madrid engineering students, in relation to their CEFR competence levels, from A2 to C1. The results obtained with the STATGRAPHICS programme serve to identify those specific grammar structures most difficult to Spanish engineering students so that their learning may be favoured. Results calibration to CERF reference levels also renders a more complete scale of linguistic competence applied to EAP contexts.